Does declining carbon‐use efficiency explain thermal acclimation of soil respiration with warming?. (22nd October 2012) - Tucker, Colin L.; Bell, Jennifer; Pendall, Elise; Ogle, Kiona
Abstract Enhanced soil respiration in response to global warming may substantially increase atmospheric CO2 concentrations above the anthropogenic contribution, depending on the mechanisms underlying the temperature sensitivity of soil respiration. Here, we compared short‐term and seasonal responses of soil respiration to a shifting thermal environment and variable substrate availability via laboratory incubations. To analyze the data from incubations, we implemented a novel process‐based model of soil respiration in a hierarchical Bayesian framework. Our process model combined a Michaelis–Menten‐type equation of substrate availability and microbial biomass with an Arrhenius‐type nonlinear temperature response function. We tested the competing hypotheses that apparent thermal acclimation of soil respiration can be explained by depletion of labile substrates in warmed soils, or that physiological acclimation reduces respiration rates. We demonstrated that short‐term apparent acclimation can be induced by substrate depletion, but that decreasing microbial biomass carbon (MBC) is also important, and lower MBC at warmer temperatures is likely due to decreased carbon‐use efficiency (CUE). Observed seasonal acclimation of soil respiration was associated with higher CUE and lower basal respiration for summer‐ vs. winter‐collected soils. Whether the observed short‐term decrease in CUE or the seasonal acclimation of CUE with increased temperatures dominates the response to long‐term warming will have important consequences for soil organic carbon storage.